A Case of Blindsight to Sight. - Chan, Adrienne (Optometry & Visual Performance, 2017)
Introduction: Visual consciousness is affected when the primary visual cortex is damaged. However, sighted behavior can persist within the areas of cortical blindness. This phenomenon is called blindsight, and it describes the ability to respond to visual stimuli in the absence of conscious awareness. With practice, visual awareness within a blind field can be trained through repeated visual stimulation. Case Report: A 70-year-old female with blindsight presented for a visual skills evaluation following a left-sided ischemic stroke. She perceived light in only very limited areas of her visual field, yet she was able accurately to identify colors, orientation, and the location of various visual targets presented in her blind field. Vision therapy was initiated to maximize the use of her residual vision, as well as to improve overall visual awareness. Within two months of starting therapy, her vision improved to 20/100 in the right eye and 20/125 in the left eye with near normal visual fields. Conclusions: With practice, responses to visual stimuli within the blind field can improve, perceptual learning can occur over time, and awareness can be trained. Rehabilitation of individuals with blindsight is highly recommended as it may present some therapeutic value as well as rehabilitative.